Comprehensive metabolomics study identifies SN-38 organ specific toxicity in mice - Xiaodong Zhu; Ya Huang; Jianguo Liu; Bo Kong; Changmeng Cui; Guangkui Han (Scientific Reports)
Abstract SN-38 (7-ethyl-10-hydroxycamptothecin), the active metabolite of irinotecan, is a crucial anticancer agent frequently studied in drug delivery systems. Irinotecan (CPT-11) is used to treat various solid tumors but is associated with adverse effects such as nausea, vomiting, diarrhea, and steatohepatitis. However, the precise biochemical pathways underlying these side effects remain unclear. To explore SN-38’s toxic mechanisms and provide insights for clinical applications of SN-38 delivery systems, we performed untargeted metabolomics to assess metabolic changes in the lungs, heart, stomach, blood, spleen, intestine, liver, and kidneys of SN-38-exposed male mice. Mice were divided into two groups: SN-38 (20 mg/kg/day intraperitoneal) and control (blank solvent). Gas chromatography-mass spectrometry (GC-MS) identified significant metabolic disturbances in all tissues. Specifically, 24, 15, 12, 21, 35, 26, 18, and 28 differential metabolites were detected in the lungs, heart, stomach, blood, spleen, intestine, liver, and kidneys, respectively. KEGG pathway enrichment revealed significant changes in metabolic pathways across these organs, particularly in purine, pyrimidine, amino acid, and glyceric acid metabolism, implicating disruptions in protein synthesis, cellular homeostasis, energy metabolism, and antioxidant defenses. This study is the first to characterize SN-38’s multi-organ toxicity using metabolomics.